Dominant lithofacies and main controlling factors of shale oil and gas enrichment in Jurassic Lianggaoshan Formation in eastern Sichuan region - XIE Bing; ZHANG Zhehao; BAI Li; FANG Chaoqiang; HE Xuquan; LUO Yanying; MIAO Xiuying; HE Guofen (Youqi dizhi yu caishoulu)
The geological reserves of shale oil from the Jurassic Lianggaoshan Formation in the eastern Sichuan region are large， but challenges of the high inhomogeneity and the unclear identification of sweet spots， etc.， seriously limit the effective exploration and development of oil and gas. Based on data from core drilling， X-ray diffraction （XRD）， scanning electron microscope （SEM）， and two-dimensional nuclear magnetic resonance （2D NMR）， the shale oil lithofacies in the Jurassic Lianggaoshan Formation in the eastern Sichuan region were finely divided， and the storage properties， oil content， and mobility characteristics of shale oil reservoirs of different lithofacies were in-depth analyzed. Then， the dominant lithofacies and the main controlling factors of oil and gas enrichment were clarified. The results show that shale oil reservoirs of the Jurassic Lianggaoshan Formation in the eastern Sichuan region develop five types of lithofacies： massive sandstone， siltstone， interlayered sand-mudstone， massive shale， and laminated shale. Among them， massive sandstone， siltstone， and interlayered sand-mudstone are ineffective reservoirs， which mainly play the role of cap rock， while massive shale and laminated shale are the dominant lithofacies in the eastern Sichuan region， belonging to typical self-generation， self-storage and micro-migration shale oil reservoirs， with high total organic carbon （TOC）， high pyrolytic hydrocarbon content， high porosity， high oil saturation， and high mobile oil saturation. The strong enrichment and high production of shale oil and gas from massive shale and laminated shale are mainly controlled by the following factors： ① The organic-rich shale is the material basis for shale oil and gas enrichment and storage in the deep-water environment of the foreland depression. ② The high vitrinite reflectance and hydrophilicity are the key factors of shale oil and gas migration and production. ③ The bedding fractures controlled by the high stratigraphic pressure are an essential guarantee for the stable and high production of shale oil and gas. The massive shale and laminated shale are the key shale oil exploration targets of the Jurassic Lianggaoshan Formation in the eastern Sichuan region.